2021
DOI: 10.1002/jat.4230
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of water skin decontamination in vivo in humans: A systematic review

Abstract: With the constant possibility of occupational exposures, chemical warfare, and targeted attacks, increased attention has been given to determining effective and timely dermal decontamination strategies. This systematic review summarises experimental studies reporting decontamination with water‐based solutions of dermal chemical contaminants with in vivo human data. Embase, MEDLINE, PubMed, Web of Science, and Google Scholar databases were comprehensively searched using search terms (“cutaneous” or “skin” or “d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Water decontaminates skin by diluting the chemical agent, rinsing of the contaminant, decreasing chemical reaction rates on the skin, minimizing metabolism and inflammation, and restoring the normal skin pH (Houston & Hendrickson, 2005). Systematic reviews by Kashetsky et al (2021), Burli et al (2021), and Chiang et al (2021), which summarize available studies with in vivo human and animal data, and in vitro human data respectively all concluded that these solutions achieve partial decontamination in the majority of decontamination outcomes (Burli et al, 2021; Chiang et al, 2021; Kashetsky et al, 2021). However, available in vivo animal data show mortality outcomes in approximately 6% of cases that used water‐only and soap and water decontamination solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Water decontaminates skin by diluting the chemical agent, rinsing of the contaminant, decreasing chemical reaction rates on the skin, minimizing metabolism and inflammation, and restoring the normal skin pH (Houston & Hendrickson, 2005). Systematic reviews by Kashetsky et al (2021), Burli et al (2021), and Chiang et al (2021), which summarize available studies with in vivo human and animal data, and in vitro human data respectively all concluded that these solutions achieve partial decontamination in the majority of decontamination outcomes (Burli et al, 2021; Chiang et al, 2021; Kashetsky et al, 2021). However, available in vivo animal data show mortality outcomes in approximately 6% of cases that used water‐only and soap and water decontamination solution.…”
Section: Discussionmentioning
confidence: 99%
“…Brent (2013) concluded through their review of clinical studies that aggressive water lavage was the best method for human corrosive dermal exposures; however, this review did not compare water lavage with other decontamination methods (Brent, 2013). Kashetsky et al (2021) summarized available in vivo human model data investigating decontamination with water‐only and soap and water solutions, finding that water alone achieved complete decontamination in only 52.6% of decontamination outcomes, whereas soap and water provided partial decontamination in 92.9% of decontamination outcomes (Kashetsky et al, 2021). Kashetsky et al (2021) concluded that water‐only and soap and water solutions provided incomplete decontamination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was later established and coined as the “wash‐in” effect, a phenomenon in which the process of skin washing paradoxically enhances skin penetration and systemic uptake, as summarized in a review by Moody and Maibach (2006). Additionally, prior reviews pending publication and conducted by Kashetsky et al (2021) and Burli et al (2021) examined the efficacy of decontamination using water‐only or water and soap solutions in in vivo human and animal models, respectively, and concluded that such methods resulted in incomplete removal of contaminants in the majority of cases. Additionally, firm conclusions regarding the efficacy of soap and water decontamination could not be drawn due to lacking absorption and excretion quantification.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on previous in vivo studies, the ‘wash‐in’ effect may be associated to a higher probability for a more rapid onset of cholinergic signs rather than considering the decontamination as ineffective (Bjarnason et al, 2008; Misik et al, 2012). The general efficacy of soap and water based skin decontamination has recently been reviewed (Burli et al, 2021; Chiang et al, 2021; Kashetsky et al, 2021).…”
Section: Introductionmentioning
confidence: 99%